Central bank independence and conservatism under uncertainty: Substitutes or complements? - Carsten Hefeker; Blandine Zimmer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
This paper revisits the trade-of between central bank independence and conservatism using a New Keynesian model with uncertainty about the central banker's output gap target. It is shown that when this uncertainty is high, the trade-of no longer holds. In this case, the optimal combination between independence and conservatism is characterised by complementarity.
Keywords: E52; E58; 330; central bank independence; conservatism; transparency of monetary policy; Geldpolitik; Regelgebundene Politik; Zentralbankautonomie; Entscheidung bei Unsicherheit; Staatliche Information; Neukeynesianische Makroökonomik; Theorie